MAQASHID SYARIAH DAN PENGEMBANGAN KEWIRAUSAHAAN BERKELANJUTAN DI INDONESIA - Aan Jaelani (UIN Siber Syekh Nurjati Cirebon, 2019)
AbstractThis article will explore the concept of maqhasid al-shari'ah and the development of sustainable entrepreneurship in Indonesia. Entrepreneurship activities are directed at achieving mashlahah or economic prosperity for each individual and society. However, the implementation of mashlahah as a conceptual framework in developing social and sustainable entrepreneurship requires criticism that can contribute practically to sharia business activities. This study uses content analysis by conducting a literature review on the theme. This paper concludes that entrepreneurship is driven by spirituality and ethical values derived from maqashid al-shari'ah which were developed into social entrepreneurship and sustainable entrepreneurship as a type of entrepreneurship that requires implementation in the form of programs and government policies in growing Muslim entrepreneurs in the era of digital technology.Keywords: Maqashid al-Shari’ah, Mashlahah, Social Entrepreneurship, and Sustainable Entrepreneurship. AbstrakArtikel ini akan mengeksplorasi konsep maqhasid al-syari’ah dan pengembangan kewirausahaan berkelanjutan di Indonesia. Kegiatan kewirausahaan diarahkan untuk mencapai mashlahah atau kesejahteraan ekonomi bagi setiap individu dan masyarakat. Namun, implementasi mashlahah ini sebagai kerangka konsepsional dalam mengembangkan kewirausahaan sosial dan berkelanjutan memerlukan kritik yang dapat berkontribusi secara praktis dalam aktivitas bisnis secara syari’ah. Studi ini menggunakan analisis konten dengan melakukan tinjauan literatur atas tema tersebut. Tulisan ini menyimpulkan bahwa kewirausahaan didorong oleh spiritualitas dan nilai-nilai etis yang diturunkan dari maqashid al-syari’ah yang dikembangkan menjadi kewirausahaan sosial dan kewirausahaan berkelanjutan sebagai jenis kewirausahaan yang membutuhkan implementasi dalam bentuk program dan kebijakan pemerintah dalam menumbuhkan entrepreneur Muslim di era teknologi digital.Kata Kunci: Maqashid al-Syari’ah, Mashlahah, Kewirausahaan Sosial, dan Kewirausahaan Berkelanjutan.